PERANAN YAYASAN PENDIDIKAN DARUL HIKAM (YPDH) CIREBON DALAM PENGELOLAAN DANA DAN ASSET SOSIAL KEAGAMAAN BAGI PEBERDAYAAN UMAT ISLAM - Fauziah Fauziah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
This article aims at understanding the role of Yayasan Pendidikan Darul Hikam (YPDH, Darul Hikam Educational Foundation) in Cirebon in managing the funds and religious social assets for the empowerment of Muslims in Cirebon. Drawing on a case study based on qualitative descriptive approach, this research concludes that some people understand the concept of waqf merely in its relation to the place of worship, not as a productive waqf. The management of funds and religious social assets of YPDH in Cirebon is good, effective and transparent. However, the access is still limited to the people, of the foundation and Muslims. YPDH in Cirebon has successfully grown their funds and religious social assets by building a kiosk, conference hall and shophouse, in which the profit can help them to equip the infrastructure of the foundation, namely by building a library, laboratory, and providing a scholarship to excellent students and those who come from deprived backgrounds, as well as creating job vacancies for the community.